“He ‘catch no ball’ leh!” Globalization versus localization in the Singaporean Translation Market - St. André, James (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractDespite the existence of local versions of English and Mandarin Chinese in Singapore, these non-standard languages are not widely used by translators and interpreters. Simultaneous court interpretation and (some) drama prove by their exception to this rule that Singapore’s translation market is driven mainly by foreign, not local demand. Further, local demand by the government and the media points to the continued prestige of “standard” English and Mandarin, where those standards are London and Beijing, respectively. Training for local translators and interpreters, then, must continue to provide students with “standard” models of these languages if they are to compete successfully for jobs in the marketplace.